Degradation of solid oxide fuel cell anodes by the deposition of potassium compounds - Hui Zhang; Ryo Yoshiie; Ichiro Naruse; Yasuaki Ueki (Carbon Resources Conversion)
Alkali contents with low melting points in the ash of woody biomass vaporize during the biomass gasification process, damaging various downstream energy conversion devices, such as the solid oxide fuel cells (SOFCs). In this study, the degradation of SOFC anodes by the deposition of potassium compounds (KCl, K2CO3, and KOH) was investigated. An aqueous solution of potassium compounds was dripped onto the anode surface of the SOFC button cell at room temperature. After drying at 343 K, 6.964 × 10-6 mol KCl, 6.964 × 10-6 mol KOH, and 3.482 × 10-6 mol K2CO3 was deposited on the anode. Button cells with the deposition of K compounds were employed for power generation experiments at 1023 K with the supply of artificial syngas from biomass gasification. After the power generation experiments, the surface structures of the anodes were microscopically analyzed using the SEM and EDS. As a result, K compounds hardly affected the OCV of SOFC. With the addition of KCl, no apparent change in the anode structure was observed, and only a slight KCl deposit was detected. However, chloride tends to be chemisorbed on Ni, increasing the ohmic resistance as well as the adsorption/desorption resistance. However, KOH transformed to K2CO3 and then remained massively on the anode, which was clearly observed in the SEM images. K2CO3 significantly decreased the cell voltage under a current density of 100 mA·cm−2. Through impedance analyses, this voltage drop was mainly attributed to the ohmic resistance and gas diffusion resistance. However, there is no evidence that this deposit degrades Ni particles.